Adjustments in the motor unit discharge behavior following neuromuscular electrical stimulation compared to voluntary contractions - Borzuola, Riccardo; Nuccio, Stefano; Scalia, Martina; Parrella, Martina; Del Vecchio, Alessandro; Bazzucchi, Ilenia; Felici, Francesco; Macaluso, Andrea (Frontiers in Physiology, 2023)
Introduction: The application of neuromuscular electrical stimulation superimposed on voluntary muscle contractions (NMES+) has demonstrated a considerable potential to enhance or restore muscle function in both healthy and individuals with neurological or orthopedic disorders. Improvements in muscle strength and power have been commonly associated with specific neural adaptations. In this study, we investigated changes in the discharge characteristics of the tibialis anterior motor units, following three acute exercises consisting of NMES+, passive NMES and voluntary isometric contractions alone. Methods: Seventeen young participants participated in the study. High-density surface electromyography was used to record myoelectric activity in the tibialis anterior muscle during trapezoidal force trajectories involving isometric contractions of ankle dorsi flexors with target forces set at 35, 50 and 70% of maximal voluntary isometric contraction (MVIC). From decomposition of the electromyographic signal, motor unit discharge rate, recruitment and derecruitment thresholds were extracted and the input-output gain of the motor neuron pool was estimated. Results: Global discharge rate increased following the isometric condition compared to baseline at 35% MVIC while it increased after all experimental conditions at 50% MVIC target force. Interestingly, at 70% MVIC target force, only NMES+ led to greater discharge rate compared to baseline. Recruitment threshold decreased after the isometric condition, although only at 50% MVIC. Input-output gain of the motor neurons of the tibialis anterior muscle was unaltered after the experimental conditions. Discussion: These results indicated that acute exercise involving NMES+ induces an increase in motor unit discharge rate, particularly when higher forces are required. This reflects an enhanced neural drive to the muscle and might be strongly related to the distinctive motor fiber recruitment characterizing NMES+.